P630 Systematic review and meta-analysis: Diagnostic delay and the subsequent impact on the disease course of adult Inflammatory Bowel Disease. (21st January 2022) - Jayasooriya, N; Ballie, S; Blackwell, J; Creese, H; Bottle, R; Petersen, I; Saxena, S; Pollok, R C
Abstract: Background: Diagnosis of inflammatory Bowel disease (IBD) can be challenging and time consuming. There is substantial variation in the reported time to diagnosis and the impact of diagnostic delay on disease course. We therefore conducted a systematic review to evaluate the length of time to diagnosis and a meta-analysis of the impact of delay on the disease course of IBD. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed, and final papers were assessed for risk of bias. We searched MEDLINE and Embase for retrospective and prospective studies, published up to December 2020, that reported diagnostic interval, from the time of symptom onset or first consultation to a confirmed diagnosis of IBD, in adults (age ≥18 years). We extracted data from published studies and calculated the weighted median and interquartile range (IQR) of the reported diagnosis interval. Delay was defined as a time period greater than the 75 th centile. From eligible studies, we extracted risk estimates and, using random-effects meta-analysis, calculated the pooled odds ratios (OR) and 95% confidence intervals (CI) of studies that examined the association of diagnostic delay with subsequent clinical outcomes, including disease phenotype and surgical intervention. Statistical heterogeneity was assessed, I 2 >50% indicating substantial heterogeneity. Results: Of 1, 533 studies identified, 28 fulfilled the eligibility criteria, including 25, 764 patients diagnosed with IBD: Crohn's disease (CD) = 13, 206 and ulcerative colitis (UC) = 12, 558. In CD, the pooled weighted median for the diagnostic interval was 8.8 months (IQR 3.0–61.1 months). In UC, the pooled weighted median was 15.2 months (IQR 2.4–62.8). Considering studies from high income countries alone, the pooled weighted median was 6.4 months (IQR 1.7–46.7) in CD, and 2.5 months (IQR 0.3–23.0) in UC. 11 studies were eligible for inclusion in the meta-analysis, representing 6, 403 patients diagnosed with IBD (CD; n = 4, 902 and UC; n = 1, 501). In CD, pooled analysis showed an association between delayed diagnosis and stricturing disease (OR:1.77, CI 1.28–2.46; I 2 =61%), penetrating disease (OR: 1.48, CI 1.21–1.82; I 2 =0%) and intestinal surgery (OR:1.88, CI 1.45–2.44; I 2 =34%; figure 1a ). In UC, delayed diagnosis was associated with an increased risk of colectomy (OR:4.13, CI 1.04–16.40; I 2 =0%; figure 1b ). Conclusion: Measures are required to reduce delay in the diagnosis of IBD, which is associated with an increase in stricturing and penetrating disease phenotype in CD and a substantially increased risk of surgery in both CD and UC.